2022
DOI: 10.1111/pbi.13869
|View full text |Cite
|
Sign up to set email alerts
|

An amino acid transporter‐like protein (OsATL15) facilitates the systematic distribution of thiamethoxam in rice for controlling the brown planthopper

Abstract: Characterization and genetic engineering of plant transporters involved in the pesticide uptake and translocation facilitate pesticide relocation to the tissue where the pests feed, thus improving the bioavailability of the agrichemicals. We aimed to identify thiamethoxam (THX) transporters in rice and modify their expression for better brown planthopper (BPH) control with less pesticide application. A yeast library expressing 1385 rice transporters was screened, leading to the identification of an amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Uptake refers to the process of pesticides entering the plant, which can be achieved through the roots or leaves; whereas, pesticide transport in plants is generally divided into intracellular and inter-organ transport [45][46][47][48] . Recently, OsATL15 was first identified to facilitate thiamethoxam uptake and systemic distribution in rice, which further confirmed that plant transporters may participate in pesticide entry into plants 49 . To take effect, herbicides must enter the plant, be translocated, and reach their target site 3 , and this process involves transporters.…”
Section: Discussionmentioning
confidence: 77%
“…Uptake refers to the process of pesticides entering the plant, which can be achieved through the roots or leaves; whereas, pesticide transport in plants is generally divided into intracellular and inter-organ transport [45][46][47][48] . Recently, OsATL15 was first identified to facilitate thiamethoxam uptake and systemic distribution in rice, which further confirmed that plant transporters may participate in pesticide entry into plants 49 . To take effect, herbicides must enter the plant, be translocated, and reach their target site 3 , and this process involves transporters.…”
Section: Discussionmentioning
confidence: 77%
“…, 2015; Xiao et al. , 2022). Our previous study demonstrated that the dendrimer‐loaded TMX showed enhanced toxicity against the non‐target pest Helicoverpa armigera (cotton bollworm) (Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…To detect the localization of OsAKR4-1, the OsAKR4-1-GFP plasmid was transfected into the rice protoplast for screening the fluorescence signal, using a Leica SP8 confocal laser scanning microscope as the parameter mentioned previously [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…In brief, all tissues were incubated overnight at 37 °C and then cleared in the 70% ethanol. The GUS-staining results were observed using a stereoscope, as described previously [ 47 ].…”
Section: Methodsmentioning
confidence: 99%